Nucleoplasmin-mediated chromatin remodelling is required for Xenopus sperm nuclei to become licensed for DNA replication - Gillespie, Peter J. (Oxford University Press, 2000)
During late mitosis and early G(1), a series of proteins are assembled onto replication origins, resulting in them becoming ‘licensed’ for replication in the subsequent S phase. Four factors have so far been identified that are required for chromatin to become functionally licensed: ORC (the origin recognition complex) and Cdc6, plus the two components of the replication licensing system RLF-M and RLF-B. Here we describe the first steps of a systematic fractionation of Xenopus egg extracts to identify all the components necessary for the assembly of licensed replication origins on Xenopus sperm nuclei (the physiological DNA substrate in this system). We have purified a new activity essential for this reaction, and have shown that it is nucleoplasmin, a previously known chromatin remodelling protein. Nucleoplasmin decondenses the sperm chromatin by removing protamines, and is required at the earliest known step in origin assembly to allow ORC to bind to the DNA. Sperm nuclei can be licensed by a combination of nucleoplasmin, RLF-M and a partially purified fraction that contains ORC, Cdc6 and RLF-B. This suggests that we are likely to have identified most of the proteins required for this assembly reaction.